MATHEMATICAL RESILIENCE AND LITERACY ABILITY THROUGH BLENDED LEARNING IN MATHEMATICS LEARNING - Sukma Murni; Dadang Juandi (Journal Of Educational Experts (JEE), 2023)
This research is motivated by the low ability of students' resilience and mathematical literacy which will affect their competence as a teacher. Amid the current conditions of the Covid-19 Pandemic, learning in schools, both in tertiary institutions, is constrained, so one of the right solutions at this time is the implementation of the Blended Learning learning model in learning, especially learning mathematics. Facing the current situation, we are required to be tough and strong, therefore we must have resilience skills so that students are resilient in facing any conditions. With the application of the Blended Learning model in mathematics learning, it is hoped that it can improve students' resilience and mathematical literacy abilities. The research method is a mixed method between qualitative built quantitative with a sequential exploratory strategy. The research instruments used were resilience questionnaire sheets and mathematical literacy test questions. The research procedure begins with qualitative data collection and then builds toward quantitative, the results of which will then be interpreted. The results showed that there was an increase in the ability of mathematical resilience and literacy using Blended Learning with a percentage of 31% and 59% respectively.